ALAT BANTU BERJALAN ERGONOMIS UNTUK MENINGKATKAN MOBILITAS ANAK TUNADAKSA DI SLBN SUNGAILIAT - Jeri Ariksa; Yudi Setiawan; Rodiawan; Fitri Sil Valen; Winda Wahyuni; Harianto (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2026)
Children with disabilities often experience mobility difficulties due to limited mobility, requiring safe, comfortable, and appropriate assistive devices. As a manifestation of their concern for improving the quality of life for children with special needs, the University-Level Community Service (PMTU) team of Bangka Belitung University conducted community service activities at Sungailiat State Special Needs School. This activity included the distribution and socialization of the use of ergonomic walking aids for students with disabilities. The devices distributed took into account ergonomic principles, safety, consideration for various age ranges, and ease of height adjustment according to the user's posture. The distribution of the devices and training on their use were carried out on August 8, 2025, accompanied by mentoring for teachers and parents to ensure optimal utilization. The results of the activity showed a positive response from the school, teachers, and parents, with the hope that these devices can improve the mobility and independence of students with special needs. This activity also strengthened collaboration between universities and special education institutions in developing appropriate technology for children with special needs.